Caddisflies (Insecta: Trichoptera) from Maranhão State, Northeast Region, Brazil: A new species, checklist, and new geographical records - Desidério, Gleison Robson; Barcelos-Silva, Patrik; de Souza, Wagner Rafael M.; Pes, Ana Maria; Azevêdo, Carlos Augusto S. De (Zootaxa, 2017)
In order to improve knowledge of Trichoptera diversity in Northeast Region, Brazil, we present here the first checklist of caddisflies from Maranhão State with a description of a new species and geographical records for the Northeast Region and for all of Brazil. Collections were made in 16 sites distributed in three municipalities of Maranhão State. A total of 54 caddisflies species, 26 genera and 10 families were recorded, including one new species of Leptoceridae, Triplectides maranhensis sp. nov., which is described and illustrated. All species listed here are recorded for the first time for the state, 23 of which are new records for the Northeast Region, as well as five new species for Brazil. These results increase the number of species reported from the Northeast Region from 167 to 221.